Results on Solutions for Several Systems of Partial Differential-Difference Equations with Two Complex Variables - Yuxian Chen; Libing Xie; Hongyan Xu (Journal of Mathematics)
This article is to describe the entire solutions of some partial differential-difference equations and systems. Some theorems about the forms of transcendental entire solutions with finite order for several high-order partial differential-difference equations (or systems) of the Fermat type with two complex variables are obtained. Moreover, some examples are provided to explain that our results are precise to some extent.